The Dilemma of Joint Property (Gono-gini) in Multi-Ethnic Marriage Communities in North Sulawesi - Salma, Salma; Alwi, Baso Mufti; Hasan, Faradila; Karim Hammad, Hamza Abed Al (Institut Agama Islam Negeri Curup, 2025)
Implementing marriage agreements in multi-ethnic communities presents complexities, particularly in harmonizing Islamic, customary, and favorable laws. The gap in understanding the concept of Syirkah Al-milk in classical fiqh and modern practice, as well as the lack of comprehensive studies on the implementation of marriage agreements in multi-ethnic areas such as North Sulawesi, creates an urgency to explore this phenomenon further. This study aims to analyze the implementation of marriage agreements from the perspective of Syirkah Al-milk and its dynamics in North Sulawesi's multi-ethnic communities. The study employed a qualitative approach with a multisite case study design across seven religious court institutions. Researchers collected data through semi-structured interviews with judges, religious figures, and traditional leaders, as well as non-participant observation and document analysis. They validated the data using method triangulation, member checking, and peer debriefing. The study found a significant gap between the concept of Syirkah Al-milk in Islamic law and its practice in society. Religious court judges face challenges harmonizing Syirkah principles with socio-cultural realities, particularly in recognizing non-financial contributions within marriage. Constitutional Court Decision No. 69/PUU-XII/2015 provides new flexibility in line with the principle of maslahah in implementing marriage agreements. The study concludes that a holistic approach integrating Sharia values, customary law, and positive law is necessary to develop a more adaptive marriage agreement system. Continuous efforts are required to increase public understanding of Syirkah Al-milk concepts and the benefits of marriage agreements.